Worldwide Protein Data Bank biocuration supporting open access to high-quality 3D structural biology data. (7th February 2018) - Young, Jasmine Y; Westbrook, John D; Feng, Zukang; Peisach, Ezra; Persikova, Irina; Sala, Raul; Sen, Sanchayita; Berrisford, John M; Swaminathan, G Jawahar; Oldfield, Thomas J; Gutmanas, Aleksandras; Igarashi, Reiko; et al.
Abstract: The Protein Data Bank (PDB) is the single global repository for experimentally determined 3D structures of biological macromolecules and their complexes with ligands. The worldwide PDB (wwPDB) is the international collaboration that manages the PDB archive according to the FAIR principles: Findability, Accessibility, Interoperability and Reusability. The wwPDB recently developed OneDep, a unified tool for deposition, validation and biocuration of structures of biological macromolecules. All data deposited to the PDB undergo critical review by wwPDB Biocurators. This article outlines the importance of biocuration for structural biology data deposited to the PDB and describes wwPDB biocuration processes and the role of expert Biocurators in sustaining a high-quality archive. Structural data submitted to the PDB are examined for self-consistency, standardized using controlled vocabularies, cross-referenced with other biological data resources and validated for scientific/technical accuracy. We illustrate how biocuration is integral to PDB data archiving, as it facilitates accurate, consistent and comprehensive representation of biological structure data, allowing efficient and effective usage by research scientists, educators, students and the curious public worldwide. Database URL : https://www.wwpdb.org/